2018
DOI: 10.1002/adom.201800077
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Quantum Dots Embedded Composite Films Enhancing UV Response of Silicon Photodetectors for Broadband and Solar‐Blind Light Detection

Abstract: In this work, the integration of in situ fabricated perovskite quantum dots embedded composite films (PQDCFs) as downshifting materials is first reported for enhancing the ultraviolet (UV) response of silicon (Si) photodetectors toward broadband and solar‐blind light detection. External quantum efficiency measurements show that the UV response of PQDCF coated Si photodiodes greatly improves from near 0% to at most of 50.6% ± 0.5% @ 290 nm. As compared to the calculated maximum value of 87%, the light coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…As a typical example, Zhong et al reported the utilization of perovskite QD (CH 3 NH 3 PbBr 3 )embedded composite films as downshifting materials to enhance the UV response of Si detectors toward obtaining broadband detection. 37 The decoration of perovskite QDs on Si photodiodes greatly boosted the EQE from an initial value of nearly 0% to approximately 50.6% ± 0.5% at 290 nm. In comparison to the peak value of 87%, the light-coupling efficiency of the hybrid device was 80% at 395 nm, indicating a strong downshifting effect that accounted for the enhanced UV photoresponse.…”
Section: Qd/simentioning
confidence: 98%
See 1 more Smart Citation
“…As a typical example, Zhong et al reported the utilization of perovskite QD (CH 3 NH 3 PbBr 3 )embedded composite films as downshifting materials to enhance the UV response of Si detectors toward obtaining broadband detection. 37 The decoration of perovskite QDs on Si photodiodes greatly boosted the EQE from an initial value of nearly 0% to approximately 50.6% ± 0.5% at 290 nm. In comparison to the peak value of 87%, the light-coupling efficiency of the hybrid device was 80% at 395 nm, indicating a strong downshifting effect that accounted for the enhanced UV photoresponse.…”
Section: Qd/simentioning
confidence: 98%
“…To enhance the detection capacity of Si photodetectors in the UV range, luminescent QDs that transform UV photons into visible light via the downshifting process are suitable materials for integration with Si. As a typical example, Zhong et al reported the utilization of perovskite QD (CH 3 NH 3 PbBr 3 )‐embedded composite films as downshifting materials to enhance the UV response of Si detectors toward obtaining broadband detection . The decoration of perovskite QDs on Si photodiodes greatly boosted the EQE from an initial value of nearly 0% to approximately 50.6% ± 0.5% at 290 nm.…”
Section: D Nanomaterial/si Heterostructurementioning
confidence: 99%
“…In addition, their bandgap can be easily tuned through the control of the CQD size, surface chemical modification, or ligand exchange . Their excellent photon‐to‐current conversion properties in the visible and near‐infrared (NIR) enable them to be used in p–n junction photodiodes such as solar cells and photodetectors . CQD‐based solar cells have been developed because of the global requirements of renewable and clean energy.…”
Section: Introductionmentioning
confidence: 99%
“…By coating the PQDCF on a Si photodiodes, response spectra was extended to UV region of 200-400 nm and the EQE was improved from near zero up to 50.6% at 290 nm. [144] Furthermore, the PQDCF can be well adapted for front-illuminated electron multiplying CCD (EMCCD) image sensors without significant resolution and response loss. By mounting solar-blind UV filter in front of the lens, we further demonstrated prototype solar-blind UV image sensor.…”
Section: Enhanced Uv Response Of Silicon Photodetectorsmentioning
confidence: 99%